The Influence of Religiosity, Personal Attitude, Subjective Norms, and Education in Developing Entrepreneurial Intention - Mokhamad Arwani; Maskudi Maskudi; Ratih Pratiwi; Ahmad Malik (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
The research aimed to analyze the effect of religiosity on subjective norms towards the entrepreneurial intention. Furthermore, the study also aimed to examine the role of personal attitude, subjective norms, and entrepreneurship education in increasing entrepreneurial intention. A sample of 220 student at Wahid Hasyim University, Semarang, Central Java, Indonesia. The sample was taken using purposive sampling, with criteria who still active and had received entrepreneurship education. The data was processed using structural equation modeling. The result show that the religiosity factor can encourage subjective norms to increase entrepreneurial intention. Furthermore, the finding show personal attitude, subjective norms, and entrepreneurship education on increasing entrepreneurial intention can contribute positively to entrepreneurial intention. The study showed that with religiosity and entrepreneurial education will positively impact entrepreneurial intention. Reliogosity is an important factor that can lead entrepreneurial intention through strengthen of subjective norms as internal supporting factor. University can increase religious students activities that can inrease their motivation to create their business. Therefore it is important to pay attention to it in higher education.